Features and risk factors for recurrence of intradural spinal tumors - V. A. Byvaltsev; I. A. Stepanov (Сибирский онкологический журнал, 2019)
Spinal cord tumors include a variety of nosological units and are classified according to their localization and histological type. The search for literature sources in the Pubmed, EMBASE and eLibrary databases demonstrated the absence of studies devoted to study of the features and risk factors for the recurrence of intradural spinal tumors. the purpose of this study was to reveal features and risk factors of recurrence of intradural spinal tumors after microneurosurgical resection. material and methods. The study included medical records of 196 patients with intradural extramedullary and intramedullary spinal tumors. The extent of microneurosurgical tumor resection, clinical efficacy of surgery, and risk factors for recurrence of intradural spinal cord tumors were been analyzed. results. Improvement in neurologic deficit after surgery was noted in 116 (59.1 %) cases, neurologic status remained the same in 47 (24.0 %) patients, and worsening of neurological deficit was observed in 33 (16.8 %) cases. Total microneurosurgical resection of intradural spinal tumors was performed in 140 (71.4 %) patients, subtotal resection in 22 (11.2 %) patients, partial resection in 25 (12.7 %) patients and spinal cord decompression or biopsy and/or its roots were performed in 9 (4.6 %) of patients. The likelihood of recurrence-free survival of patients with benign intradural spinal cord tumors was significantly higher than that of patients with malignant tumors (p<0.001). Benign tumors (χ2=34.7, p<0.05), thoracic and lumbosacral tumors (χ2=10.3, p<0.05), low degree of neurological deficit (χ2=31.5, p<0.05), absence of syringomyelia/syringobulbia signs (χ2=13,2, p<0,05), as well as extramedullary tumors (χ2=12,6, p<0.05) allowed us to perform total degree microneurosurgical resection. Malignant tumors (χ2=34.8, p<0.05), cervical and thoracic tumors (χ2=8,4, p<0,05), high degree of neurological deficit (χ2=12,9, p<0.05), partial resection, biopsy or decompression of neural structures (χ2=9.7, p<0.05) and intramedullary tumors statistically significantly increased the risk of their recurrence. conclusion. Histological pattern, tumor localization, preoperative clinical and neurological deficit according to the McCormick classification and the extent of surgery are significant risk factors for recurrence of intradural spinal tumors.